Paralympic Games: Evolution of sport and social event - Marsero, W. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
The Paralympic Games born after the Second World War in the United Kingdom and they had a different aim from nowadays. In fact, in 1948 Sir Ludwig Guttman, the medical manager of the National Spinal Injuries Centre of Stoke Mandeville who was convinced that the deep psychic depression could made patients` clinical conditions worse, introduced the sport as a therapy. After four years, he organized a real tournament between the paraplegics of the National Spinal Injuries Centre and other paraplegics coming from Holland. At the same time in the United States the Professor Timothy J. Nugent, University of Illinois, organized a wheelchair basketball tournament in 1949. In 1956 these Games were acknowledged by the I.O.C. and in 1960 they had placed in Rome, just after the Olympic Games. From that moment, the Paralympic Games run the course of the Olympic ones, and took place every four years after them. The Paralympic Games of Turin 2006 included 5 sport disciplines (Alpine Skiing, Nordic Skiing, Biathlon, Ice Sledge Hockey, Wheelchair Curling) and will take place in four competition places (Torino, Sestriere, Pragelato, Pinerolo). The organization of an event, as big as the Olympic Games are, has to consider the requirements of all the users, in absolute normality. This is the reason why the carrying out of Turin 2006 Olympic and Paralympic Games is directed towards the contemporaneous success of both the events at the same time. The right accessibility for the Olympic system has permitted us to rationalize all the efforts and have a good preparation of the subsequent Paralympic event, making both of them "normalized" for the "different" involved users. In both cases, some interventions were made on: accessibility, sport and support facilities, hospitality, reception, security and sanitary inspection systems. In any case, the constructions have to be planned for their utilization after 2006 and the users, they are intended for, will be always athletes (or some different users after 2006), people assigned to the activities and to the upkeep of the facilities, companions and audience. It must be assured the accessibility to all these people by the current law and the requirements coming from the Olympic and Paralympic Committees. We resorted to different expedients, according to the post-Olympic utilization (flats, colleges, holyday camps), and these will be used without any further adjustments during the final reconversion, as accessibility is concerned. A similar principle has been adopted as regards road system and pathways, even if we met with more difficulties to conform some existent buildings. In order to obtain the maximum uniformity, during the interventions, we launched a dialogue with different involved workers to estimate the efficacy together with them. It has been paid particular attention to Games` sporting aspect according to the classification that is used to screen competitions and athletes. They are divided in sitting, standing e blind. At the same time, besides the planning aspects, it has been done a lot of work to inform, to awaken and to involve the population about the Paralympic Games and the sport activities for people with disability. From some years, it has been organized in Turin the sport event of the Paralympic Day, during which there took place some competitions and the demonstration of some sport disciplines that are played by athletes with disability. Besides, there were prearranged some education projects for every grade of school to promote the Paralympic Games and the sport for people with disability, making a comparison with the same sports for able-bodies. In every case the opportunity to organize such an event as Turin 2006 Olympic and Paralympic Games, was the unrepeatable occasion to test those principles of normality that favour the knocking down of every kind of barriers. Besides it was the chance to make more hospitable and usable our region to the totality of people.